Secondary Metabolites in Soil Ecology - Karlovsky, Petr (Soil Biology,, 2008)
Secondary Metabolites in Soil Ecology focuses on the role of bacterial, fungal and plant secondary metabolites in soil ecosystems. Our understanding of the biological function of secondary metabolites is surprisingly limited, considering our knowledge of their structural diversity and pharmaceutically relevant activities. This volume reviews functional aspects of secondary metabolite production, with a focus on interactions among soil organisms. Topics such as truffle metabolites and burnt phenomenon, ecology of mycotoxins in soil, root exudates, and chemical interactions between Streptomyces and mycorrhiza fungi are treated. Further aspects are the role of microbial metabolites as quorum sensing signals, their role in protecting plants against pathogens and the effect of volatiles on soil invertebrates. Chapters describing techniques for the detection of antibiotics in soil and the application of metabolomics to rhizosphere research, which has advanced rapidly in recent years, complement the book.